Cognitive Imprecision and Strategic Behavior - Cary D. Frydman; Salvatore Nunnari (Center for Economic Studies and ifo Institute (CESifo), 2021)
We propose and experimentally test a theory of strategic behavior in which players are cognitively imprecise and perceive a fundamental parameter with noise. We focus on 2 x 2 coordination games, which generate multiple equilibria when perception is precise. When adding a small amount of cognitive imprecision to the model, we obtain a unique equilibrium where players use a simple cutoff strategy. The model further predicts that behavior is context-dependent: players implement the unique equilibrium strategy with noise, and the noise decreases in fundamental volatility. Our experimental data strongly support this novel prediction and reject several alterna-tive game-theoretic models that do not predict context-dependence. We also find that subjects are aware of other players' imprecision, which is key to generating strategic uncertainty. Our framework has important implications for the literature on global games and, more broadly, illuminates the role of perception in generating both random and context-dependent behavior in games.
Keywords: C72; C92; D91; E71; 330; perception; efficient coding; coordination; global games